ASSOCIATION BETWEEN THE PRESENCE OF COMORBIDITIES AND CARDIOVASCULAR OUTCOMES IN A HYPERTENSIVE LATIN AMERICAN POPULATION. (June 2022) - de Sousa, Andrea; Magalhães, Fabrício Galdino; da Silva, Suelen Benta; Inuzuka, Sayuri; Teixeira, Maria Emília; Batista, Sandro Rodrigues; Barroso, Souza Weimar Kunz Sebba; Sousa, Ana Luiza Lima
Abstract : Objective: To analyze the association between the presence of comorbidities and cardiovascular outcomes in hypertensive Latin American patients. Design and method: A cross-sectional study with a sample of patients from the First Brazilian Hypertension Registry (I RBH), that recruited patients aged 18 and over, diagnosed with hypertension for at least 4 weeks. Participants were followed for one year in public and private services. Comorbidities were categorized as hypertension associated with diabetes mellitus or dyslipidemia (2 morbidities) and hypertension with diabetes mellitus and dyslipidemia (3 morbidities). The association of morbidity combinations with the following cardiovascular outcomes was performed: acute myocardial infarction, angina, heart failure and myocardial revascularization. Data were analyzed using the chi-square test and a significance level of p < 0.05. Results: The sample consisted of 2.642 patients aged 61 ± 11.8 years. Within the evaluated sample of hypertensive patients, dyslipidemia (46.9%) was the most prevalent, followed by diabetes mellitus (29.7%). The triad hypertension, diabetes and dyslipidemia was present in 19% of participants and responded for the highest prevalence of cardiovascular outcomes: acute myocardial infarction (21.7%, p < 0.001), angina (7.8%, p = 0.02), heart failure (7.6%, p < 0.001) and myocardial revascularization (14.7%, p < 0.001). Conclusions: Acute myocardial infarction was the most present outcome among hypertensive and diabetic patients. Cardiovascular outcomes were associated with of other morbidities in addition to hypertension.